Flexibilidade espacial : barreiras para seu emprego em habitações de interesse social na cidade de Cuiabá, a partir do Programa Minha Casa, Minha Vida - Costa, Heliara Aparecida (2015)
This research aims to identify and analyze the barriers to the use of the concept of architectural flexibility in social housing. The investigation is focused on Program Minha Casa Minha Vida (PMCMV), launched in Brazil in 2009, taking the city of Cuiabá, Mato Grosso. The PMCMV was born with the aim of reducing the housing deficit and boost the Brazilian economy. Official figures disclose that already have been delivered 2.17 million dwellings and over 1.68 million are already contracted, with R$ 254.5 billion investment. However, this fact could represent a fertile time for innovation and quality improvement of the housing project for low-income population, has been repeating past formulas. Similar to what occurs in the country in Cuiaba accommodation units are standardized, serial and designed with increasingly tight spaces, with arrangements that are limited to the functional aspect. Family composition, behavior and current and future needs of customization are not considered in the design and production of housing. The result is a recurring format with rigid features, where adaptations can occur only through costly and complicated reforms, with negative impacts on aesthetic and functional quality housing. The concept of flexibility as an alternative to customization by the owner, who also represents criteria for project quality is not even contemplated. Thus, to meet the proposed goal, this study is a qualitative research method, with in-depth interviews with those involved in the production process: direct (Ministério das Cidades, Caixa Econômica Federal, builders, architects, state and municipal institutions) and indirect (teachers and specialists). The results show that the barriers are due to: lack of the concept of flexibility; disregard for the low-income public; lack of interest in general; legal criteria; lack of architect; professional qualification; technology; extreme functionality; lack of market relationship; little exchange between the market and the gym; lack of personnel structure and low technical capacity of the public sphere; partiality in relations with box builders; contractual issues; reversal of roles between public and private actors; cultural factors; financial factors; political factors; and image in the media. Are issues that contribute to a critical reflection on the subject and attract the attention of those involved in the production process of these buildings to the concept of flexibility.